Hydrogels with prestressed tensegrity structures - Bin Xue; Xu Han; Haoqi Zhu; Qingtai Li; Yu Zhang; Ming Bai; Ying Li; Yiran Li; Meng Qin; Tasuku Nakajima; Wei Wang; Jian Ping Gong; et al. (Nature Communications)
Abstract Tensegrity structures are isolated rigid compression components held in place by a continuous network of tensile components, and are central to natural systems such as the extracellular matrix and the cell cytoskeleton. These structures enable the nonreciprocal mechanical properties essential for dynamic biological functions. Here, we introduce a synthetic approach to engineer hydrogels with tensegrity architectures, drawing inspiration from the mechanochemical principles underlying biological systems. By employing in-situ enzyme-induced amino acid crystal growth within preformed polymeric networks, we achieve a hierarchical integration of micro crystal sticks randomly interlocked in the prestressed polymer matrice. This design mirrors natural tensegrity structures, balancing mechanical forces to maintain high stiffness (tensile moduli up to 30 MPa), fracture toughness (2600 J m⁻²), and water content (exceeding 80%). The resultant hydrogels exhibit bimodulus behavior due to their tensegrity structure, featuring a tensile-to-compressive modulus ratio of 13. This biomimetic approach provides a strategy for creating robust, adaptive materials for applications in tissue engineering and beyond.